Chemical Vapor Deposition Growth of 2D Transition Metal Dichalcogenides on 3D Substrates toward Electrocatalytic‐Related Applications - Lijie Zhu (Wiley-VCH, 2021)
Recently, 2D transition metal dichalcogenides (TMDCs) have emerged as promising materials for energy‐related applications, due to their fascinating properties such as abundant catalytic active sites, large specific surface area, and low cost. To promote these applications, the scalable preparation of 2D TMDCs is an essential issue. Chemical vapor deposition (CVD) has been proved to be a powerful method for the syntheses of TMDCs with designable morphologies, controllable layer thicknesses, tunable phases, etc. In the CVD growth process, the morphologies, structures, and compositions of substrates play crucial roles in modulating the geometric features and physical/chemical properties of the resultant TMDCs products. Comparing with commonly used lamellar substrates, 3D‐architectured substrates show great potentials for tailoring the morphologies and properties of TMDCs, due to their large specific surface areas, designable structures, and variable compositions, etc. In this topical review, the introduction of recent progresses in the CVD growth of TMDCs on 3D substrates, as well as their applications in electrochemical hydrogen evolution reaction (HER) is focused. The current challenges and future research directions in this research area are also discussed.